Are type-2 biomarkers of any help in asthma diagnosis?. Issue 2 (20th July 2020) - Nekoee, Haleh; Graulich, Emmanuel; Schleich, Florence; Guissard, Françoise; Paulus, Virginie; Henket, Monique; Donneau, Anne Françoise; Louis, Renaud
Asthma is a common chronic airway disease, the diagnosis of which remains challenging, as recently highlighted by the great proportion of both under- and overdiagnosis [1]. The current diagnosis is based on the conjunction of suggestive symptoms and the demonstration of an excessive airway calibre fluctuation either by a bronchodilation test or by a bronchial challenge [2, 3]. T2 biomarkers lack the accuracy to make an asthma diagnosis in patients with suggestive symptoms https://bit.ly/3hYnnHu